Phytochemical Constituents from the Seeds of Capsella bursa-pastoris and Their Antioxidant Activities - Zhou, Ti-Qiang; Wei, Zhen-Zhen; Zhang, Jin-Rui; Dong, Jia-Hui; Liu, Chun-Ying; Jiang, Cong-Zhi; Xia, Zi-Ming; Liu, Si-Fan; Li, Min; Zhang, Guang-jie; Chen, Li; Tian, Ying; et al. (Plant foods for human nutrition (Dordrecht), 2023)
Phytochemical investigation of 70% EtOH extract of the seeds of Capsella bursa-pastoris led to the isolation of a new cyclobutane organic acid ( 1 ), and fourteen known compounds, including two organosulfur compounds ( 2 , 3 ), two quinonoids ( 4 , 5 ), five flavonoids ( 6 - 10 ), three sterols ( 11 - 13 ) and two other types ( 14 , 15 ). The structures of the compounds were elucidated by extensive spectroscopic analyses as well as comparison of their spectroscopic data with those reported in the literature. The antioxidant capacities of all compounds and extractive fractions were evaluated by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging test and ferric reducing antioxidant power (FRAP) assay. Then the antioxidative substances were evaluated for their neuroprotective effects against H 2 O 2 -induced HT22 cell injury. The results indicated the strong scavenging ability to free radical of the extractive fractions and compounds 1 - 3 , 8 - 10 and 13 , and the ferric reducing antioxidant power of the extractive fractions and compounds 1 - 3 , 8 and 10, which were close to or higher than that of the positive control trolox. The EtOAc fraction, n -BuOH fraction, and compounds 1 , 3 and 8 can protect HT-22 cells from oxidative damage. Graphical abstract